If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -8 = -3x + -24 Reorder the terms: -8 + 5x = -3x + -24 Reorder the terms: -8 + 5x = -24 + -3x Solving -8 + 5x = -24 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -8 + 5x + 3x = -24 + -3x + 3x Combine like terms: 5x + 3x = 8x -8 + 8x = -24 + -3x + 3x Combine like terms: -3x + 3x = 0 -8 + 8x = -24 + 0 -8 + 8x = -24 Add '8' to each side of the equation. -8 + 8 + 8x = -24 + 8 Combine like terms: -8 + 8 = 0 0 + 8x = -24 + 8 8x = -24 + 8 Combine like terms: -24 + 8 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 5y+10=3y+30 | | 9y-6=-24 | | 8x+12=6x+16 | | x^3-xb-4=0 | | b^3-3b-4=0 | | -6x+2y=6 | | 12-2x=34 | | 2x+8=6x-4 | | 3x+17=50 | | 2x+13=-57-8 | | 0.16+3n=0.29+n | | 4=2x+y | | 0.6-3x=0.3+2x | | (2x+4)2=(x-1)2 | | y=-5t^2+10t+15 | | -7-2x+6=-2x | | 2.7x-1.8=1.8x+2.7 | | 2.7x-1.8=1.8k+2.7 | | 2x+1=4x+2 | | n^3+3n^2+3n+2=0 | | 7x-14=-9 | | 2(x+5)+3(x-2)=64 | | 4x^3+15x^2+3x+28=0 | | 4x^2+15x+3=0 | | 2x*5y=50 | | -5/16/25/8= | | 5/8-(1/2-3/4)= | | 10(-3+-2t)+10+-2(6t+-13)=0 | | x(x^2-9)=0 | | 10(-3-2t)+10-2(6t-13)=3 | | -0.2x^2+0.1x=-0.06 | | -5z^2-4z+3=0 |